The Concept of Holistic Education in the Thoughts of Syed Muhammad Naquib al-Attas and Its Relevance in the Modern Era - Atika Kusuma Wardani; Nur Allya; Muhammad Nizaruddin; Fahri Hidayat (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Contemporary educational challenges extend beyond academic quality to include a declining emphasis on character formation and spiritual values. The dominant focus on cognitive achievement and practical skills has created an imbalance in educational goals, contributing to moral crises and the fragmentation of knowledge. In this context, the thought of Syed Muhammad Naquib al-Attas offers a holistic educational framework through the concept of ta’dib, which centers on the cultivation of proper conduct as the foundation of human development. This study aims to examine Al-Attas’s concept of holistic education and evaluate its relevance in addressing contemporary educational challenges. The research employs a qualitative approach using library research, drawing on Al-Attas’s works and related scholarly literature. Data were collected through documentation and analyzed using content analysis, without involving field participants. The findings indicate that Al-Attas’s educational framework emphasizes the integration of intellectual, moral, and spiritual dimensions through the internalization of adab. It also rejects the dichotomy between religious and secular knowledge, positioning education as a process of forming a complete human being. These results suggest that a ta’dib based educational approach remains highly relevant in responding to globalization and ongoing character-related issues in modern education. Therefore, Al-Attas’s thought provides a strong conceptual foundation for developing an integrative, value-oriented, and contextually responsive educational system.